Preoperative neutrophil/lymphocyte ratio and prognostic nutritional index predict survival in patients with non-small cell lung cancer - Shimizu, Katsuhiko (World J Surg Oncol, 2015)
BACKGROUND: The immunological status, consisting of “inflammation status” and “nutritional condition,” is important for the survival of patients with various cancers, including non-small cell lung cancer (NSCLC). The neutrophil/lymphocyte ratio (NLR) reflects the inflammation status, and the prognostic nutritional index (PNI) reflects the immunological nutritional condition. In the present study, the correlation between the NLR and the PNI as well as the consistency and magnitude of the prognostic impact of the NLR and the PNI were investigated. METHODS: We conducted a retrospective review of data from 334 patients who had undergone a curative resection for NSCLC. The NLR and the PNI were calculated, which was routinely performed before surgery. The correlations between the NLR and the PNI and survival were then evaluated. RESULTS: A clear inverse correlation was observed between the NLR and the PNI. The NLR was associated with sex, smoking history, the CEA level, tumor size, and vascular invasion. The PNI was associated with sex, age, smoking history, tumor size, histological type, tumor differentiation, and vascular invasion. Patients with NLR ≥2.5 had a significantly poorer survival outcome, and patients with PNI <50 had a significantly poorer survival outcome. A multivariate analysis demonstrated that age, nodal metastasis, tumor differentiation, NLR, and PNI were independent predictors of disease-free and overall survival. CONCLUSIONS: Our study demonstrated a significant inverse correlation between the NLR and the PNI, and a high NLR and a low PNI were significantly associated with a poor survival among patients who had undergone a complete resection for NSCLC.